Radiation-induced extracellular matrix remodelling drives prognosis and predicts radiotherapy response in muscle-invasive bladder cancer - Guerrero Quiles, Conrado; Fahy, Siobhan; Bartak, Matej; Gonzalez Abalos, Julia; Powell, Emilia; Lodhi, T.; Reed, Rachel; Reeves, Kim; Baker, Alex; James, Nicholas D.; Hall, Emma; Huddart, Robert A.; et al. (Frontiers in Oncology, 2025)
Muscle-invasive bladder cancer (MIBC) is a prevalent disease that can be treated with radiotherapy, but has a poor prognosis. Radiation-induced extracellular matrix (ECM) remodelling and fibrosis can induce tumour resistance and recurrence, but have not been studied in MIBC. Here, we aimed to characterise the impact of radiation on the ECM composition of MIBC. Three MIBC cell lines (T24, UMUC3, J82) were treated with fractionated radiation. We used proteomics to analyse the ECM composition produced by surviving cancer cells and immunofluorescence to investigate changes in the morphology and number of ECM fibres. We evaluated the RNA expression of identified ECM proteins (FN1, COL5A1, COL1A1, TNF6AIP6, FLG) in one cystectomy (TCGA-BLCA, n=397) and two radiotherapy (BC2001, n=313; BCON, n=151) cohorts. There were 613 proteins affected by radiation (padj<0.05, fold change >2 or <-2), 68 of which were ECM-associated proteins. There was a general increase in proteases and protease regulators but heterogeneity across cell lines. Enrichment analysis showed ECM organisation was the primary pathway affected. Immunofluorescence confirmed radiation affected ECM structure, generally, reducing the number, length and width of fibres. Five ECM genes of interest were identified (COL1A1, COL5A2, FN1, FLG, TNFAIP6), constituting an ECM signature. High FN1, COL1A1, TNF6AIP6 mRNA levels and ECM signature scores were independent poor prognostic markers, while FLG mRNA expression independently predicted radiotherapy benefit in a meta-analysis (n=861). We found high COL1A1 expression levels predicted hypoxia-modifying treatment benefit. Prognostic significance of COL5A2, FN1 and the ECM signature was dependent on patients harbouring TP53-mutations. Radiation alters the composition and structure of the ECM produced by MIBC. As a proof-of-concept, we showed that radiation-affected ECM genes are independent prognostic and predictive markers of radiotherapy benefit in MIBC. Future studies should validate these radiation-induced ECM changes in clinical samples, and explore the role of FLG in radioresistance.